2020
DOI: 10.14283/jnhrs.2020.28
|View full text |Cite
|
Sign up to set email alerts
|

Using International Collaborations to Shape Research and Innovation Into Care Homes in Brazil: A White Paper

Abstract: England and the Netherlands, which have 0.12 and 0.23 beds per head of population over the age of 80 years respectively (6).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…3500 institutional care facilities represents 0.03 beds per capita of the population aged 80 years and above. Given that fact, less than 1% of the elderly population is living in institutional care facilities (Avila, 2017; Jacinto et al, 2020). De Oliveira et al (2017) found the quality of care in Brazilian institutional care facilities varied remarkably and left ample room for improvement.…”
Section: Resultsmentioning
confidence: 99%
“…3500 institutional care facilities represents 0.03 beds per capita of the population aged 80 years and above. Given that fact, less than 1% of the elderly population is living in institutional care facilities (Avila, 2017; Jacinto et al, 2020). De Oliveira et al (2017) found the quality of care in Brazilian institutional care facilities varied remarkably and left ample room for improvement.…”
Section: Resultsmentioning
confidence: 99%
“…Most LTCF reduced these activities, reinforcing that the functionality of residents was not a priority. Moreover, Brazilian LTCF do not require health professionals as employees 34 or have the structure or human resources to provide specific health care needed during the COVID-19 pandemic. 35 Thus, the demand for care related to functionality is evident in older adults living in LTCF.…”
Section: Discussionmentioning
confidence: 99%
“…The LTCI sector in Brazil is also underdeveloped with 64% of the municipalities without any care homes and a national ratio of 8.732 older adults (>75 years) per care home, that varies widely between regions (Lacerda et al, 2021). Without sufficient number of care homes and evidence on LTCI, the quality of care provided to the Brazilian old residents might be below the adequate standards (Jacinto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%